Reliable Code Generation and Test Environment demonstrated on a PI-Controller Design - Schwarz, M. H.; Sheng, H.; Ustoglu, I; Chabaan, W.; Boercsoek, J. (ELSEVIER SCIENCE BV, 2016)
This paper focuses on the latest version of a tool developed within the department to guide developer through the various steps of requirements, test-procedures and documentations to finally download the derived algorithm on a safety programmable logic controller (PLC). Requirements on how to develop and how to test software are steadily increasing due to international standards, which have to be obeyed in industries in general, and in the process- and automation industries in particular. A simple model is derived to be used to develop a PI controller that has to pass several steps to be qualified for execution on a PLC. The paper explains the different steps and describes the various problems that might occur. (C) 2016, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.
Keywords: safety; reliability; automated code generation; PI control; international standards; PREDICTIVE CONTROL; Automation & Control Systems